Effects of the use of medicinal plants in pregnant women: a review (Research, Society and Development, 2022)
During pregnancy, the female body undergoes biochemical, physiological, and structural changes that require increased attention to ensure good development and maintenance of maternal and fetal health. During this period, women are more sensitive and, therefore, are more likely to experience symptoms that are recurrent at this stage (nausea, nausea, headaches, insomnia, among others). To minimize or put an end to these symptoms, pregnant women make use of plants with medicinal properties, which depending on the type or way in which it is administered, may be able to induce embryotoxic, teratogenic and abortifacient effects. Objective: To investigate the effects of the use of medicinal plants in pregnant women through a bibliographic survey of the specialized literature. Method: This is a narrative review of the literature, original and review scientific articles were selected in the time interval between the years 2012 and 2022. Obtained through research in the main electronic and open access databases: PUBMED, SCIELO, BIREME, LILACS. Results: Some studies showed that the knowledge of pregnant women regarding the action of some herbs is minimal or non-existent. And that plant species such as chamomile, cinnamon, fennel, ginger, mint, and pomegranate have in their composition, substances that can cause abortion in pregnant women. Conclusion: In view of the above, it is understood that the lack of information is one of the main factors that strengthens the use of some herbs during pregnancy, endangering maternal and fetal health.